Development of Science Learning Tools Based on Ethnoscience to Improve Students' Science Literacy and Environmental Awareness - Firmansah Firmansah; Muslimin Muslimin; Ardi Rahmawan; Widia Widia (Lembaga Bale Literasi, 2025)
Science literacy is the ability to use scientific knowledge, identify questions, and draw conclusions based on evidence in order to understand and make decisions regarding natural phenomena. While environmental awareness is a change in thinking, attitudes, and behavior towards the surrounding environment, However, based on the results of observations and observations of phenomena that occur in society, environmental awareness is very low, and the conditions in the world of education lately are very concerning. So the purpose of this study is to develop science learning tools based on ethnoscience to improve science literacy and environmental awareness of students at the junior high school level. This study also involves students and lecturers carrying out activities outside the campus as part of the Main Performance Indicators of Higher Education. And supports SDGs, namely quality education and utilization of the environment and culture. The results of the pretest showed that the average student science literacy was 60, while the average score of environmental awareness was 55. This shows that students' understanding of the concept of science and environmental awareness is still relatively low before the implementation of ethnoscience-based learning. After the treatment was carried out, the results of the posttest using ethnoscience-based learning devices were obtained; there was an increase in the average score of scientific literacy to 80 and environmental awareness to 85. This increase shows the effectiveness of ethnoscience-based learning devices in improving students' scientific literacy and environmental awareness. Meanwhile, the results of student responses showed positive results with an average score of 4.5 on a scale of 1–5. Students stated that the material presented in ethnoscience-based learning devices was interesting, easy to understand, and relevant to everyday life.